Анализ процесса пуска в имитационной модели вентильно-индукторного двигателя - Галайко, Лидия Петровна (НТУ "ХПИ", 2014)
В статье рассматривается вопрос анализа влияния закона изменения управляющих параметров на характер переходных процессов в режиме пуска в вентильно-индукторном двигателе рудничного электровоза с помощью разработанных моделей для программы Simulink пакета программ Matlab. Приведены результаты расчетов на этих моделях для двигателя мощностью 27 кВт и частотой вращения 1215 об/мин.

The question of analysis of influence of law of change of control parameters on the character of transients in the mode of starting of a Swithed Reluctanse Motor of a miner electric locomotive by means of models developed for the program Simulink package of program Matlab is considered. Results of calculations by these models for a motor by power of 27 kW and by frequency of rotation 1215 rev/min are presented. Results over of calculation are brought for the direct starting at permanent control parameters and for the control starting. The direct starting does not provide the receipt of the required set mode and accompanied by the considerable pulsations of moment. The control starting provides the required set mode and allows to decrease the pulsations of moment.
The analysis of a process of a starting in a simulation model of a switched reluctance motors
Keywords: вентильно-индукторный двигатель; режим пуска; программа Simulink; пульсации момента; switched reluctance motor; regime of a starting; program Simulink